The Role of Teachers in Optimizing the Talents and Interests of Students in Madrasah Ibtidaiyah - Vindy Agung Trisnawa; Nasrul Fuad Erfansyah; Munawir Munawir; Uswatun Chasanah; Makhillah Makhillah (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2025)
This study aims to describe the role of classroom teachers in optimising students’ talents and interests at MIN 2 Sidoarjo. The research employed a qualitative descriptive approach using field research methods, including observation, interviews, and documentation involving Grade V classroom teachers (VA, VB, and VC). The findings reveal that classroom teachers perform four key roles: facilitators, innovators, motivators, and communicators in supporting students’ potential development. These roles are implemented through differentiated learning practices, emotional support, and effective communication with students and parents. The study highlights the strategic contribution of classroom teachers as the main agents of talent and interest development in madrasah ibtidaiyah that lack guidance counsellors. The findings imply that strengthening teachers’ pedagogical competence in differentiated and student-centred learning is essential to support holistic student development in Islamic elementary education